Tiến tới xây dựng các công viên địa chất ở Việt Nam : lược khảo về các di sản địa mạo - An Lê Đức (Vietnam Journal of Earth Sciences, 2008)
Towards the establishement of Geological Parks in Viet Nam : preliminary studying on geomorphological heritages